ÚTMUTATÓ A MEGMARADÁSHOZ : A REGÁTI MAGYAR DIASZPÓRA KALENDÁRIUMA - Makkai, Béla (Közép-Európai Közlemények, 2020)
The Big Illustrated Calendar of the Hungarians living in Romania used to be an informative-educational printed paper launched by the Hungarian government, as part of the so-called national defense strategy in 1901. The Calendar, which was loyal to the host country, was published according to the needs of the emigrant workers. Furthermore, its main aim was to strengthen the emigrants’ relationship with the home country with its literary pieces and lifestyle-management related articles. The Calendar played a significant part in strengthening the Hungarian identity until the incursion of the Romanians in 1916.